An Investigation of Video and Audio to Improve Students' Motivation in Learning Listening during Online Learning at Ban Pongneeb School, Thailand - Wardhana, Yessy Yustia; Muhammad, Ribeh Najib (Universitas Muhammadiyah Gresik, 2021)
The importance and usefulness of incorporating video media elements to teach listening have become part of the general understanding and common place in education nowadays (Alonso, 2013; Garcia, 2012; Macwan, 2015). Videos have been widely used in education, with videos of students making it easier to understand the material, and also audio is media to give message toward hearing. As we know that students are always feel trouble before trying listening lessons, or they are always feel bored with listening lessons. The purpose of this study is to examine students’ perception of their motivation in learning listening by using audio media and video media. Motivation is a crucial factor and very important factor in learning, students will not interest in learning if they don’t have any motivation. The participant of this study was four grade students from Ban Pongneeb School, Loei, Thailand. The questionnaire and interview were conducted in collecting the data for this study. The result shows that the majority of the students perceive that video media is a great tool for improving their motivation in learning listening, but an occasional the use of audio media in learning listening should not be rejected.